Proceedings of 1994 IEEE International Reliability Physics Symposium RELPHY-94 1994
DOI: 10.1109/relphy.1994.307834
|View full text |Cite
|
Sign up to set email alerts
|

Two electromigration failure modes in polycrystalline aluminum interconnects

Abstract: Grain-boundary (GB) erosion-type voids and transgranular slit-like voids are found to be two competing elecaomigration (EM) failure modes in partly-bamboo interconnects. The effects of metal microstructure, passivation thickness, line width and length, and EM sbess conditions on the two failure modes were studied. The kinetics for GBtype failures is strongly affected by the threshold effect in polycrystalline segments and is well described by the MultiLognormal (MLN) function with stress-dependent number of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Several studies have shown that in Al(Cu) technology with near-bamboo grain structure interfacial diffusion, along the edges of the lines, plays a more significant role in the transport of metal ions compared to grain boundaries [for instance : Hu 1993aand 1993b, Atakov 1994]. …”
Section: Influence Of Microstructure On Emmentioning
confidence: 99%
“…Several studies have shown that in Al(Cu) technology with near-bamboo grain structure interfacial diffusion, along the edges of the lines, plays a more significant role in the transport of metal ions compared to grain boundaries [for instance : Hu 1993aand 1993b, Atakov 1994]. …”
Section: Influence Of Microstructure On Emmentioning
confidence: 99%
“…In Blech's study, it was found that j th is inversely proportional to the line length l, whereby the threshold length product j th ·l is used to assess EM damage. In addition, from EM tests using Al line-type samples covered with passivation, the relation between j th ·l and temperature was presented, which indicated that j th ·l was lower and there was more EM damage at higher temperature (Blech, 1976 andAtakov, et al, 1994). Many factors are thought to affect the temperature dependence of j th ·l.…”
Section: Introductionmentioning
confidence: 99%